Karyological Characteristics of Some Endemic Onobrychis Taxa Belonging to Onobrychis Section Naturally Grown in Turkey - Onur İleri; Süleyman Avcı (Turkish Journal of Agriculture: Food Science and Technology, 2018)
Karyotype properties of of six endemic Onobrychis taxa (O. beata, O. cilicica, O. fallax, O. podperae, O. sulphurea and O. lasistanica) naturally grown in Turkey were determined using squash preparation method and similarity of these endemics with cultivated taxon (O. viciifolia) were revealed. Ploidy levels of Onobrychis taxa were diploid (2n=14) except O. lasistanica and O. viciifolia (2n=28). Basic chromosome number is x=7 and chromosomes ranged from median to sub median with regard to centromere position. While the longest total chromosome length was measured in O. cilicica (28.21 µm), the shortest total chromosome length was in O. beata (21.47 µm). O. cilicica and O. sulphurea have satellite on chromosome 1 and chromosome 2, respectively. Hierarchical cluster analysis was performed to determine the relationships among the Onobrychis taxa and they were separated into three groups. O. fallax, and O. podperae were in the first group while O. sulphurea and O. cilicica were in the second group. O. beata, O. lasistanica, and O. viciifolia were assigned to the third group.